Development of 3D Monopoly Media the Influence of the Environment on the Type of Livelihood of the Population of Class IV Elementary School - Cholifah, Puri Selfi; Prakasa, Yanuar Galih; Khotimah, Khusnul (Proceedings Series of Educational Studies, 2024)
The purpose of this development research is to produce picture story media on kingdom material that is valid according to material experts and media experts, as well as interesting and practical for users. This type of research is Research and Development (RnD). The ADDIE model used in this research consists of five stages: analysis, design, development, implementation, and evaluation. Based on the results of product validation by material experts and media experts, the final scores were 100% and 93,75%, respectively. In addition, based on the final assessment by users, namely teachers and students, regarding the practicality and attractiveness of the product, the final scores were 92.51% and 92.59%, respectively. Based on the results of the validation and assessment, this research and development of picture story media produces media that is feasible, practical, and interesting for grade IV elementary school students.. Keywords: Social Studies; Learning Media; Monopoly 3D